2018
DOI: 10.1101/347823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lineage segregation, pluripotency and X-chromosome inactivation in the pig pre-gastrulation embryo

Abstract: 5High-resolution molecular programs delineating the cellular foundations of and then of epiblast and hypoblast in late blastocysts. We detected distinct 3 3 pluripotent states, first as a short 'naïve' state followed by a protracted primed state. comprehending early human development and a foundation for further studies of 3 7 human pluripotent stem cell differentiation in pig interspecies chimeras. . CC-BY-NC-ND 4.0 International license It is made available under a (which was not peer-reviewed) is the au… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…S7C). The expression pattern was similar to SOX2, suggesting that a similar interaction mechanism might exist in Epiblast [35]. Our results also reveal that the overexpression of KDM3A can significantly improve the proliferation and anti-apoptosis ability of pluripotent stem cells, but that of KDM3B leads to a decline in cell proliferation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…S7C). The expression pattern was similar to SOX2, suggesting that a similar interaction mechanism might exist in Epiblast [35]. Our results also reveal that the overexpression of KDM3A can significantly improve the proliferation and anti-apoptosis ability of pluripotent stem cells, but that of KDM3B leads to a decline in cell proliferation.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies on pig early embryos have indicated that OCT4 is generic expressed in ICM and TE, which differs from that in humans and mice (Fig. S7C) [35]. The regulatory mechanism of endogenous OCT4 in pigs may be unique.…”
Section: Discussionmentioning
confidence: 94%
“…This could be because naive pluripotency has not been appropriately instated in donor cells [17,27]. In contrast, host blastocysts at the time of embryo injection may not be developmentally synchronized with putative donor naive cells [28]. In this regard, the nature of chimera competency in primates may fundamentally differ from the rodent paradigm, such that currently defined ''naivete'' does not correspond to chimera-forming ability.…”
mentioning
confidence: 99%